Special 35 years of the Federal Constitution (Revista do Tribunal Regional Federal da 3ª Região, 2023)
It is with great satisfaction that we have the privilege of presenting the 158th edition of the Journal of the Federal Regional Court 3rd Region, specially prepared in celebration of the 35th anniversary of the promulgation of the 1988 Federal Constitution. Indeed, this milestone is an opportune moment for us to reflect on the advances that the "Citizen Constitution" represented in the construction of the Democratic Rule of Law, as well as on the challenges that remain and the future prospects in the constitutional sphere. In this context, it is important to demonstrate the commitment of this Federal Court to Brazilian constitutionalism. Therefore, this edition includes articles on constitutional matters in their many facets - tax, social security, civil and criminal law, among others. In addition, a section of selected case law has been added, bringing together paradigmatic judgments on the same theme from all the Sections. Finally, it is essential to highlight that this commemorative edition represents the completion of a project to optimize the services provided by this Office, which culminated in the implementation of the Open Journal Systems (OJS) platform. The new system will enable a fully electronic editorial process, which will increase the dissemination of the Journal's content, more quickly and with higher quality, with the aim of collaborating with the legal debate, not only within the Judiciary, but also in the academic sphere, with the aim of reaching the whole of society.
Keywords: Federal Constitution; 35 years of the Constitution; commemorative edition